Traditional Journalism Norms Revisited: Journalistic Reconceptualizations of Objectivity - Velloso, Carolina (The Journal of communication inquiry, 2026)
This study uses a theoretical framework grounded in alternatives to normative objectivity to investigate whether and how journalists call for a reimagining of objectivity as an operational framework for journalism. Through a textual analysis of 289 metajournalistic articles and X posts produced between 2012 and 2022, the study also compares how those discourses have (or have not) shifted within that decade. Findings indicate that calls to reimagine objectivity as a journalistic norm steadily increased in volume and gravity over the time period, with two critical incidents prompting a groundswell of discourse: The 2016 presidential election and the murder of George Floyd in 2020. It also found that the metajournalistic discourse on X was distinct but complementary to the discourse in the articles. This study shows that journalists are arguing for an alternative paradigm that retains a commitment to truth, facts, and accuracy during the newsgathering process, but conceptually acknowledges that no kind of knowledge production is inherently value-free, and thus values journalists’ standpoints as an asset, rather than a hindrance, to news coverage.